2021
DOI: 10.1016/j.neurol.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical description of the broad range of neurological presentations of COVID-19: A retrospective case series

Abstract: Background: Neurological disorders associated with SARS-CoV-2 infection represent a clinical challenge because they encompass a broad neurological spectrum and may occur before the diagnosis of COVID-19. Methods: In this monocentric retrospective case series, medical records from patients with acute neurological disorders associated with SARS-CoV-2 infection from medicine departments of an academic center in Paris area were collected between March 15th and May 15th 2020. Diagnosis of SARS-CoV-2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This is consistent with other studies. [ 4 12 ] In this study, although cerebral venous sinus thrombosis (CVT) formed just 2.1% of the cohort, there were more patients with CVT who were COVID-19 positive, and this association is not new. [ 13 ] There were significantly more patients with meningitis who were COVID-19 positive.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with other studies. [ 4 12 ] In this study, although cerebral venous sinus thrombosis (CVT) formed just 2.1% of the cohort, there were more patients with CVT who were COVID-19 positive, and this association is not new. [ 13 ] There were significantly more patients with meningitis who were COVID-19 positive.…”
Section: Discussionmentioning
confidence: 92%
“…Meppiel et al stated that neurological manifestations occurred after the first symptom of COVID-19, with a mean delay of 7 days for encephalitis, 12 days for acute ischemic cerebrovascular syndrome, and 18 days for GBS 14 . On the other hand, there are studies reporting that various neurological manifestations can occur in patients infected with SARS-CoV-2 without clinical manifestations of respiratory dysfunction 32 . In a review, it was concluded that patients with COVID-19 may develop neurological manifestations before, during, and even after the onset of common symptoms of COVID-19 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor is the delay between the onset of neurological complications and the confirmation of SARS-CoV-2 infection, which was addressed in a study and found that confirmation of SARS-CoV-2 infection was delayed, on average, by 1.6 days from the onset of neurological manifestations, whereas in the case of encephalitis the delay was 3.9 days and 2.7 days for cerebrovascular events 32 . In the case of patient 3, diagnosed with encephalitis, the infection was confirmed only 7 days after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Encephalitis is marked by elevated levels of proinflammatory cytokines, chemokines, interleukin-6, interleukin-1, interleukin-18, TNF-α, CXCL10, with serological abnormalities of c-reactive protein, procalcitonin, D-dimer, and ferritin being particularly associated with increased risk of severity and mortality (13)(14)(15)(16)(17).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Additionally, COVID-19-associated encephalitis can produce hyperintensities in the mesial temporal lobe, subcortical white matter, brainstem, and claustrum (14).…”
Section: Clinical Featuresmentioning
confidence: 99%